Implementation of the Use of DAU through the BPKH Benefit Program to Improve Hajj Services - Zain, Aviva Nur; Yuliar, Ade; Saidun, Muhammad (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
This study aims to determine the use of the value of the benefits of endowment funds for the people through the BPKH benefit program and to find out what obstacles were encountered during the implementation of the particular benefit program within the scope of the pilgrimage services. In this research, using qualitative research methods. Then the data sources of this research are primary and secondary by using purposive sampling technique . Data collection techniques with observation, interviews and documentation. As for testing the validity of the data with source triangulation. Meanwhile, to analyze data with data reduction (data reduction), data presentation (data display) , drawing conclusions (conclusion drawing/verification). The use of the value of the benefit of the people's endowment fund is managed by the BPKH Health Division in collaboration with organizations in in terms of benefit partners to be distributed to beneficiaries who support the benefit program, namely specifically for pilgrimage service activities. The use of DAU benefit values that have been explicitly realised for the scope of Hajj services in 2021 such as the procurement of operational cars for KBIHU offices, procurement of data digitization and KBIHU digitization infrastructure in collaboration through PPPA Daarul Qur'an benefit partners.***Penelitian ini bertujuan untuk mengetahui penggunaan nilai manfaat dana abadi umat melalui program kemaslahatan BPKH dan mengetahui kendala apa saja yang dihadapi selama berjalannya program kemaslahatan khusus ruang lingkup pelayanan ibadah haji. Dalam penelitian ini, menggunakan metode penelitian kualitatif. Kemudian sumber data penelitian ini adalah primer dan sekunder dengan menggunakan teknik purposive sampling. Teknik pengumpulan data dengan observasi, wawancara dan dokumentasi. Adapun dalam uji keabsahan data dengan triangulasi sumber. Sedangkan untuk menganalisis data dengan reduksi data (data reduction), penyajian data (data display), penarikan kesimpulan (conclusion drawing/verification). Penggunaan nilai manfaat dana abadi umat ini dikelola oleh Divisi Bidang Kemaslahatan BPKH yang bekerjasama dengan organisasi-organisasi di dalam istilah mitra kemaslahatan untuk disalurkan kepada penerima manfaat yang mendukung program kemaslahatan yaitu khusus untuk kegiatan pelayanan ibadah haji. Penggunaan nilai manfaat DAU yang sudah terealisasi khusus ruang lingkup pelayanan ibadah haji pada tahun 2021 seperti pengadaan mobil operasional untuk kantor KBIHU, pengadaan digitalisasi data dan sarana prasarana digitalisasi KBIHU yang bekerjasama melalui mitra kemaslahatan PPPA Daarul Qur’an.Keywords: People’s Endowment Fund, Hajj Service, BPKH Benefit Program.